2002
DOI: 10.1128/jcm.40.1.75-79.2002
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Meningococcal Carriage by Culture and PCR of Throat Swabs and Mouth Gargles

Abstract: The standard method for detecting meningococcal carriage is culture of throat swabs on selective media, but the levels of carriage determined depend heavily on the skills of the individuals taking the swab and interpreting the cultures. This study aimed to determine the most sensitive detection method for meningococcal carriage. Throat swabs and saline mouth gargles, obtained from 89 university students, were processed in parallel by conventional culture and TaqMan ctrA PCR. Carriage of meningococci, as detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
39
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 12 publications
0
39
0
1
Order By: Relevance
“…All N. meningitidis isolates were tested using an rt-PCR assay targeting the porA (encoding the class 1 or PorA protein) and ctrA genes (76,77). All isolates (regardless of porA and ctrA results) were evaluated further in rt-PCR assays specific for the eight capsule serogroups, as described by Rojas et al (68).…”
Section: Meningococcalmentioning
confidence: 99%
“…All N. meningitidis isolates were tested using an rt-PCR assay targeting the porA (encoding the class 1 or PorA protein) and ctrA genes (76,77). All isolates (regardless of porA and ctrA results) were evaluated further in rt-PCR assays specific for the eight capsule serogroups, as described by Rojas et al (68).…”
Section: Meningococcalmentioning
confidence: 99%
“…verse primer ( Table 1) described by Corless et al (4) and demonstrated to amplify a region of the ctrA gene from all meningococcal serogroups (4,11).…”
mentioning
confidence: 99%
“…Genes specific for N. meningitidis detection and genogrouping. ctrA or porA genes have been used individually to identify N. meningitidis (15,16). However, we found that our primers based on the ctrA sequence produced PCR products from both N. meningitidis and N. lactamica, and those based on the porA sequence gave PCR products from both N. meningitidis and N. gonorrhoeae (data not shown).…”
Section: Methodsmentioning
confidence: 56%
“…Infections with N. meningitidis are a significant cause of mortality and morbidity in young children and adolescents (16,23). The bacterial capsular polysaccharide (CPS) is the most important virulence factor for N. meningitidis (14,20,26,28,32).…”
mentioning
confidence: 99%
See 1 more Smart Citation